The importance of financial institutions for the development of the brazilian Amazon: an application of the social accounting matrix - CARVALHO, André Cutrim (Universidad Alberto Hurtado, 2022)
The fundamental purpose of this article is intended to measure the economic impacts that the regional financial institutions are providing along the chain of values of the productive activities located in the Brazilian Amazon and their impacts on economic activities through the Social Accounting Matrix. The main conclusion is that to break the status quo in the region, it is necessary to set a national regional development policy that favors the formation of vertically integrated production chains and a trade policy that encourages the export of most products value-added so that the benefits arising can be internalized in the Brazilian Amazon in the form of income and employment.